STIMULATION OF INNOVATIVE WORK BEHAVIOR: THE ROLE OF TRANSFORMATIONAL LEADERSHIP AND INTRINSIC MOTIVATION WITH CREATIVE SELF-EFFICACY AS MEDIATION - Nisrina Windiyani; Indah Lestari; Ahmad (MANAJEMEN DEWANTARA, 2025)
Knowing how innovative work behaviour (IWB), intrinsic motivation (IM), and transformational leadership (TL) relate to creative self-efficacy (CSE) and providing empirical insight into the factors that drive innovation among civil servants are the objectives of this study. A quantitative descriptive approach was used, with data collected through questionnaires from 99 ASNs at the Regional Secretariat (SETDA) of Lebak Regency using SEM-PLS version 3.0. used to evaluate the structural model (inner model) and measurement (outer model). The results showed that there was no positive relationship between TL and IM on IWB. However, TL and IM have a positive influence on CSE. Furthermore, CSE plays a mediating role in the relationship between TL and IWB as well as between IM and IWB. These results highlight the importance of CSE in fostering innovation in the workplace and help organisational leaders to consider other factors that influence IWB. Keywords: Transformational Leadership, Intrinsic Motivation, Creative Self-Efficacy, Innovative Work Behavior.